ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF POSBINDU NON-COMMUNICABLE DISEASES - Ika Suciatmi; Arwani; Budi Widiyanto (Jurnal Health Sains, 2024)
The cause of death of approximately 71% (36 million) people per year is due to non-communicable diseases. The 2018 Riskesdas data shows an increase in key NCD indicators. The significant increase in NCDs is expected to add to the burden on both the public and the government in healthcare financing. According to Government Regulation No. 71 of 2015, the prevention and control of NCDs are to be carried out through community health efforts and individual health efforts. The prevention and control of NCDs in the community are implemented through the activities of the NCD Posbindu. This research analyzes the factors affecting the performance of NCD Posbindu. The research method used is a Cross-Sectional approach with a quantitative method. The population consists of 486 NCD Posbindu, and the research sample uses Total Sampling, consisting of 29 NCD Posbindu. Data analysis includes univariate, bivariate (Spearman Rank), and multivariate (Multiple Linear Regression). The research results show that the majority of NCD Posbindu's performance falls into the "good" category, with 17 (58.62%), while the human resources (HR) are good in 19 (65.50%) cases, infrastructure is good in 12 (41.38%) cases, and the budget is good in 16 (53.20%) cases. Human resources, infrastructure, and the budget are positively and significantly correlated with the performance of NCD Posbindu, with correlation coefficients of HR (r=0.688), infrastructure (r=0.650), and the budget (r=0.598). The results of the Multiple Linear Regression test reveal that human resources, infrastructure, and the budget, when considered together, collectively affect the performance of NCD Posbindu, with an F value of 7.240, an adjusted R-squared value of 0.401, and a regression coefficient (β) of 18.799. Human resources, infrastructure, and the budget are related and significantly influence the performance of NCD Posbindu by 40.1%.